Study of the Effect of Water Intake by the Matrix on the Optimization of the Fiber Matrix Interface Damage for a Composite Material by Genetic Algorithms - Temimi Lahouari, H.; Allel, M.; Belkaid, N.; Boutaous, A.; Bnuamrane, R. (Проблемы прочности, 2013)
The objective of this paper is study the influence of the matrix swelling due to water on the damage of the fiber matrix interface of a composite material. The results obtained by a genetic approach based on Weibull probabilistic model, show good agreement between the simulation and the actual behavior of the two materials T300/914 and PEEK/APC2. Also the absorption of water by the matrix increases significantly the interface damage.